1993
DOI: 10.1139/v93-180
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the oxidation of alcohols by ferrate ion

Abstract: A kinetic study of the reduction of ferrate ion under basic conditions has been completed. The observation that a typical aliphatic ether, tetrahydrofuran, is oxidized at a rate comparable to that of aliphatic alcohols, such as cyclopentanol, indicates that the reaction between ferrate and alcohols is likely initiated by attack of the oxidant at an a-C-H bond, a conclusion that is consistent with the occurrence of primary deuterium kinetic isotope effects (2.8-4.3 at 25°C) when a-hydrogens are replaced by deut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 0 publications
4
60
0
Order By: Relevance
“…Figure 8 clearly indicated that HFeO 4 -and FeO 4 2-species are predominant species in neutral and alkaline solutions, at which the Fe(VI) was known to be relatively stable towards its spontaneous dissociation [37]. The ferrate salts when dissolved in water, oxygen is evolved and ferric hydroxide is precipitated (equation (14)).…”
Section: Speciation and Decomposition Of Fe(vi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 clearly indicated that HFeO 4 -and FeO 4 2-species are predominant species in neutral and alkaline solutions, at which the Fe(VI) was known to be relatively stable towards its spontaneous dissociation [37]. The ferrate salts when dissolved in water, oxygen is evolved and ferric hydroxide is precipitated (equation (14)).…”
Section: Speciation and Decomposition Of Fe(vi)mentioning
confidence: 99%
“…The lowest rate of decomposition was occurred at pH higher than ~9-10, while it increased significantly at lower pH values [35,38]. The reaction kinetics followed second-order below pH 9.0, while first order above pH 10.0 [37]. The decomposition of ferrate(VI) hence, described by the following equilibrium and kinetic models [36]: (20) Reactions clearly showed that the forward reactions (15) to (20) (except reaction (16)) are relatively slow steps hence, could be the rate determining steps.…”
Section: Speciation and Decomposition Of Fe(vi)mentioning
confidence: 99%
“…The experiments were conducted in the pH range 8.5-10.0. The rate of spontaneous decomposition of Fe(VI) in water at pH ≥ 8.5 does not contribute significantly in studying the photocatalytic reduction of Fe(VI) in an alkaline medium [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…K 2 FeO 4 has been reported to oxidize a variety of organic functional groups such as amines and particularly alcohols, for which a number of publications can be found in the literature (Audette et al 1971(Audette et al , 1972Kim et al 1984Kim et al , 1986Lee and Gai 1993;Delaude et al 1995;Delaude and Laszlo 1996;Caddick et al 2000;Takehiro et al 2001;Song and Wang 2003;Song et al 2006a). Studies involving K 2 FeO 4 generally employ alkaline aqueous conditions (Audette et al 1971(Audette et al , 1972Takehiro et al 2001;Song et al 2004) in which K 2 FeO 4 is very soluble but unstable.…”
Section: Introductionmentioning
confidence: 99%